Alterations in brain activation patterns in women with functional defecatory disorder: A novel fMRI rectal balloon expulsion study. Issue 12 (27th April 2022) - Neshatian, Leila; Karmonik, Christof; Khavari, Rose; Shi, Zhaoyue; Elias, Saba; Boone, Timothy; Quigley, Eamonn M. M.
Abstract: Background: Functional defecatory disorders (FDD) are common among women. Despite the extensive research on peripheral mechanisms involved in FDD, the central–neural contribution to its pathophysiology remains poorly understood. We aimed to delineate specific supra‐spinal regions involved in defecation and examine whether their activity, as measured by blood‐oxygen‐level‐dependent (BOLD) signals, is different in FDD. Methods: We performed functional MRI (fMRI) with concurrent rectal manometry in 15 controls and 18 females with ROME III diagnosis of FDD. A block design was used and brain activation maps based on BOLD effect employing the generalized linear model were calculated for each subject. Statistical significance between groups was assessed by a Student t ‐test with cluster‐based multiple comparisons correction (corrected p  < 0.01). Key Results: Simulated defecation was associated with activation of regions of primary and supplementary motor (SMA) and somatosensory cortices, homeostatic afferent (thalamus, mid‐cingulate cortex, and insula), and emotional arousal networks (hippocampus and prefrontal cortex), occipital and cerebellum along with deactivation of right anterior cingulate cortex (ACC) in controls. Women with FDD had fewer regions engaged in defecation and BOLD activation was much decreased is areas related to executive‐cognitive function (insula, parietal, and prefrontal cortices). Patients unlike controls showed activation in right ACC and otherwise had similar brain activation patterns during anal squeeze. Conclusions & Inferences: Our results provide evidence that distinct differences exist in supra‐spinal control of defecation in key regions of motivational‐affective regulation and executive‐cognitive function, in patients with FDD as compared to controls. Abstract : Functional MRI with concurrent rectal manometry in 15 healthy controls and 18 women with ROME III diagnosis of functional defecatory disorder (FDD) revealed activation of homeostatic afferent and emotional visceral networks responsible for perception of gut signals, along with executive‐cognitive responses to these stimuli at defecation. The observed fMRI patterns showed significant differences in integration of neuronal circuitry for affect regulation and executive function (thalamus, insula, SMA, and prefrontal cortex) in FDD, suggesting a role for cognitive control and management of uncomfortable emotions rather than motor execution in the pathophysiology of FDD.